Komposisi Populasi Lalat Buah (Diptera: Tephritidae) dan Parasitoid yang Berasosiasi dengan Tanaman Mangga (Mangifera indica L.) di Beberapa Kabupaten Provinsi Bali - I MADE MEGA ADNYANA; I WAYAN SUSILA; LIDYA ELYSABET (Fakultas Pertanian Universitas Udayana, 2023)
Population Composition of Fruit Flies (Diptera: Tephritidae) And Parasitoids Associated with Mango Plants (Mangifera indica L.) in Several Regencies of Bali Province. This research aims to determine the types of fruit flies (Bactrocera spp.), parasitoids, abundance, percentage of damage and parasitization parasitoids of fruit flies in Badung Regency, Jembrana and Tabanan. The research was conducted purposively by taking fruits that have symptoms of fruit fly damage in the yard in Badung, Jembrana and Tabanan Regency. The research was conducted from September 2020 to February 2021. The results of study found 3 species of fruit flies that damaged mangoes in Badung, Jembrana and Tabanan Regencies, namely B. dorsalis (Hendel), B. carambolae (Drew & Hancock) and B. albistrigata (De Meijere). Two species of Bactrocera were found in Badung Regency, namely B. dorsalis (86.3%) and B. carambolae (13.7%). Jembrana Regency are B. dorsalis (82.03%), B. carambolae (15.7%) and B. albistrigata (2.9%). Tabanan Regency are B. dorsalis (80.84%) and B. carambolae (19.15%). Percentage of fruit fly damage in Tabanan Regency was 35.08%, Jembrana Regency was 33.56% and Badung Regency was 32.57%. Parasitoids found in Badung, Jembrana and Tabanan Regencies are Fopius arisanus and Diachasmimorpha longicaudata. Parasitization rate of parasitoids respectively in Tabanan Regency was 6.8%, Jembrana Regency was 5.9% and Badung Regency was 5.1%.